Dataset of de novo assembly and functional annotation of the transcriptome during germination and initial growth of seedlings of Myrciaria Dubia “camu-camu” - Castro Gómez, Juan Carlos (2020)
Myrciaria dubia “camu-camu” is a native shrub of the Amazon that is commonly found in areas that are flooded for three to four months during the annual hydrological cycle. This plant species is exceptional for its capacity to biosynthesize and accumulate important quantities of a variety of health-promoting phytochemicals, especially vitamin C [1], yet few genomic resources are available [2]. Here we provide the dataset of a de novo assembly and functional annotation of the transcriptome from a pool of samples obtained from seeds during the germination process and seedlings during the initial growth (until one month after germination). Total RNA/mRNA was purified from different types of plant materials (i.e., imbibited seeds, germinated seeds, and seedlings of one, two, three, and four weeks old), pooled in equimolar ratio to generate the cDNA library and RNA paired-end sequencing was conducted on an Illumina HiSeq™2500 platform. The transcriptome was de novo assembled using Trinity v2.9.1 and SuperTranscripts v2.9.1. A total of 21,161 transcripts were assembled ranging in size from 500 to 10,001 bp with a N50 value of 1,485 bp. Completeness of the assembly dataset was assessed using the Benchmarking Universal Single-Copy Orthologs (BUSCO) software v2/v3. Finally, the assembled transcripts were functionally annotated using TransDecoder v3.0.1 and the web-based platforms Kyoto Encyclopedia of Genes and Genomes (KEGG) Automatic Annotation Server (KAAS), and FunctionAnnotator.